The effect of egg size on yolk utilization and growth of rainbow trout alevins (Oncorhynchus mykiss Walbaum) - Çalta, M (Akademiai Kiado, 2001)
Changes in body weight and yolk weight were studied in rainbow trout alevins derived from large eggs (diameter >4 mm) and small eggs (egg diameter <4 mm) from the same female. Maximal body weight was reached later, and was higher, for alevins derived from large than from small eggs. The yolk was absorbed more quickly by the alevins of small eggs. Percentage of body water increased in alevins during fasting up to a limit of 91%. Although the limit was the same for both groups of alevins, it was reached more quickly by alevins from small eggs. Relative water content of the yolk did not seem to be influenced by egg size. These results suggest that original egg size had both a quantitative and qualitative effect on the early development of alevins.
Keywords: egg size; yolk utilization; growth; Oncorhynchus mykiss; rainbow trout; alevin